Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 5 - Section 5.2 - Negative Exponents and Scientific Notation - Exercise Set - Page 354: 54



Work Step by Step

$\frac{5^{-1}z^{7}}{5^{-2}z^{9}}=\frac{5^{-1}}{5^{-2}}\times\frac{z^{7}}{z^{9}}=5^{-1-(-2)}\times z^{7-9}=5^{-1+2}\times z^{-2}=5^{1}\times z^{-2}=5\times \frac{1}{z^{2}}=\frac{5}{z^{2}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.